Human induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) for modeling cardiac arrhythmias: strengths, challenges and potential solutions - Joshi, Jyotsna; Albers, Cora; Smole, Nathan; Guo, Shuliang; Smith, Sakima A. (Frontiers in Physiology, 2024)
Ion channels and cytoskeletal proteins in the cardiac dyad play a critical role in maintaining excitation-contraction (E-C) coupling and in providing cardiac homeostasis. However, functional changes in these dyad proteins, whether induced by genetic, epigenetic, metabolic, therapeutic, or environmental factors disrupt normal cardiac electrophysiology, leading to abnormal E-C coupling and arrhythmias. Animal models and heterologous cell cultures provide platforms to elucidate the pathogenesis of arrhythmias for basic cardiac research; however, these traditional systems do not truly reflect human cardiac electro-pathophysiology. Notably, patients with the same genetic variants of inherited channelopathies (ICC) often exhibit incomplete penetrance and variable expressivity which underscores the need to establish patient-specific disease models to comprehend the mechanistic pathways of arrhythmias and determine personalized therapies. Patient-specific induced pluripotent stem cells-derived cardiomyocytes (iPSC-CMs) inherit the genetic background of the patient and reflect the electrophysiological characteristics of the native cardiomyocytes. Thus, iPSC-CMs provide an innovative and translational platform in cardiac disease modeling and therapeutic screening. In this review, we will examine how patient-specific iPSC-CMs historically evolved to model arrhythmia syndromes in a dish, and their utility in understanding the role of specific ion channels and their functional characteristics in causing arrhythmias. We will also examine utility of CRISPR/Cas9 to establish patient-independent, variant-induced arrhythmia models. Next, we will examine the limitations of using human iPSC-CMs with respect to in vitro arrhythmia modeling that stems from variations in iPSCs or toxicity due to gene editing on iPSC or iPSC-CMs and explore how such hurdles are being addressed. Importantly, we will also discuss how novel 3D iPSC-CM models better capture in vivo characteristics and how all-optical platforms provide non-invasive and high-throughput electrophysiological data that is useful for stratification of emerging arrhythmogenic variants and drug discovery. Finally, we will examine strategies to improve iPSC-CM maturity, including powerful gene editing and optogenetic tools that can introduce/modify specific ion channels in the iPSC-CMs and tailor cellular and functional characteristics. We anticipate that an elegant synergy of iPSCs, novel gene editing, 3D-culture models, and all-optical platforms will offer a high-throughput template to faithfully recapitulate in vivo arrhythmogenic events necessary for personalized arrhythmia monitoring and drug screening.